The relational regulation of within‐person variation in personality expression. Issue 2 (28th July 2021) - Lakey, Brian; Hubbard, Sultan Ali; Brummans, Jessica; Obreiter, Amy; Perrin, Paul B.
Abstract: There is renewed interest in how people express different levels of personality across situations or times (within‐person variation). However, within‐person studies typically do not focus on the specific relationship partners that are linked to the expression of personality. To remedy this, we applied relational regulation theory (RRT) to the study of within‐person variation. RRT states that specific relationship partners are important social contexts for understanding within‐person variation and describes how people regulate their affect, action and thought through interacting with or thinking about specific partners. In three studies of students ( N s = 136, 349, 110), participants rated their levels of six‐ or five‐factor personality dimensions when with or thinking about different relationship partners. Personality expression was strongly consistent across partners. Yet, in each study, there were also strong effects whereby more extraversion, agreeableness and openness were expressed when with some partners but not others. In each study, when a recipient saw a relationship as supportive, the recipient expressed more extraversion, agreeableness, and openness. Effects for emotionality and conscientiousness were less consistent. Theoretical implications for RRT and within‐person variation in personality were discussed.